Revealing Dynamic Surface and Subsurface Reconstruction of High-Entropy Alloy Electrocatalysts during the Oxygen Evolution Reaction at the Atomic Scale - Luan, Chenglong; Escalera-López, Daniel; Hagemann, Ulrich; Kostka, Aleksander; Laplanche, Guillaume; Wu, Dongshuang; Cherevko, Serhiy; Li, Tong (ACS Catalysis, 2024)
High-entropy alloys (HEAs) represent a promising material systems in the search for next-generation high-performance oxygen evolution reaction (OER) electrocatalysts. Developing HEA electrocatalysts requires a thorough understanding of surface and subsurface reconstruction during the OER and their effects on activity and stability. However, it is difficult for most characterization techniques to resolve the atomic-scale elemental distribution of multiple elements and their surface composition. Herein, we combine atom probe tomography and transmission electron microscopy with online and offline inductively coupled plasma mass spectrometry to unveil the surface and subsurface reconstructions of a model CrMnFeCoNi Cantor alloy electrocatalyst during the OER. We reveal that the Cantor alloy suffers from dissolution once in contact with the electrolyte, whereby the surface is deficit in Cr, Mn, and Co before the OER. At the onset of the OER cycling, the Cantor alloy surface is activated by forming an ∼5 nm amorphous NiFe-rich (oxy)hydroxide. Below the surface (oxy)hydroxide, an ∼3 nm Cr-rich oxide layer and an oxygen-rich layer (∼3-5 nm) are formed in the subsurfaces, which impede the outward diffusion of Mn, Fe, Co, and Ni to the surface, retarding their continuous dissolution from the bulk, while Cr dissolution occurs steadily. As the OER proceeds, the Cr-rich oxide layer collapses due to steady Cr dissolution, which results in the exfoliation of the amorphous (oxy)hydroxide layer. Simultaneously, the fastest diffusing Mn segregates to the surface, forming a Mn-rich oxide, which leads to a deterioration in the OER activity. Our atomic-scale data advance the fundamental understanding of how concerted thermodynamically and kinetically driven elementary processes occur for different elements in HEAs during the OER. More importantly, our study highlights the importance of establishing the structure-activity-stability correlations of HEA electrocatalysts during the OER in order to validate the hypothesis of synergistic effects in enhancing their activity and stability.
CRIS-Team Scopus Importer:2024-08-16
Keywords: atom probe tomography; compositionally complex alloys; dissolution; oxyhydroxides; stability